Ethnocultural heritage of Belarus as a platform for tourism branding - Irina V. Olunina (RUDN Journal of World History)
The author analyzes the current experience of creating tourism brands in the regions of Belarus based on elements of ethnocultural heritage. Various strategies for demonstrating and interpreting the Belarusian ethnocultural heritage in local tourism brands are considered as a powerful tool for attracting tourists and obtaining unique and authentic experiences. The role of the ethnocultural heritage of Belarus in the formation of local tourism brands is revealed. The main disadvantage of tourism branding in Belarus is the lack of consistency in building a strategy. The main task of increasing the efficiency of the tourism branding process is to minimize the negative impact of tourism, respect for local culture and traditions, and find a balance between using of cultural heritage elements for tourism and their preservation. The ethnocultural heritage of Belarus as a tourism branding platform contributes to the preservation and popularization of cultural heritage, economic development of local communities, education and enlightenment of tourists, strengthening the identity of local residents, expanding tourism infrastructure and attracting new categories of tourists.